Analisis Pelaporan Keuangan Segmentasi PT.Indofood Sukses Makmur Tbk: Indonesia - Putri, Cindy Fredicia; Indonesia, Indonesia; Citra, Yolanda; Juliani, Hesti; Murtaib, Agum; Rodiah, Siti (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
Financial reporting is one of the activities carried out by companies that have gone public, financial reporting can assist users in making decisions or policies to develop activities. Segment and interim financial statements are one of the reports that need to be disclosed in the company's financial statements. The purpose of segment and interim financial reports is to provide information about the different types of business activities and the economic environment in which the company operates. Fulfillment of this objective will help users of financial statements to better understand the company's performance and assess future cash flow prospects, as well as be able to make more informed judgments about the company as a whole. The purpose of this study is to analyze the determination of reporting segments using the ten percent test on revenue and profit and loss in the financial statements of PT.Indofood Sukses Makmur Tbk for 2018-2022 in accordance with PSAK number 5. The research method used is a qualitative research method, the sample used is a purposive sampling technique, which is a sampling technique with certain considerations. The sample taken comes from the Financial Statements of PT.Indofood Sukses Makmur Tbk segment which consists of 4 segments namely Branded Consumer Products, Bogasari, Agribusiness and Distribution. The research results show that the distribution segment does not need to be reported because it does not pass the 10% test on income for 5 years (2018-2022), the agribusiness segment and the distribution segment do not pass the 10% test on profit and loss in 2018 and 2019 but in 2020, 2021 ,2022 the agribusiness segment passed the 10% test on profit and loss, and the 10% test on distribution segment assets did not pass the test for 5 years (2018–2022). And the bogasari segment only in 2020 did not pass the 10% test on assets.